Tff3 Deficiency Differentially Affects the Morphology of Male and Female Intestines in a Long-Term High-Fat-Diet-Fed Mouse Model. - Šešelja, Kate; Bazina, Iva; Vrecl, Milka; Farger, Jessica; Schicht, Martin; Paulsen, Friedrich; Baus Lončar, Mirela; Pirman, Tatjana (International Journal of Molecular Sciences, 2023)
Trefoil factor family protein 3 (Tff3) protects the gastrointestinal mucosa and has a complex mode of action in different tissues. Here, we aimed to determine the effect of Tff3 deficiency on intestinal tissues in a long-term high-fat-diet (HFD)-fed model. A novel congenic strain without additional metabolically relevant mutations (Tff3-/-/C57Bl6NCrl strain, male and female) was used. Wild type (Wt) and Tff3-deficient mice of both sexes were fed a HFD for 36 weeks. Long-term feeding of a HFD induces different effects on the intestinal structure of Tff3-deficient male and female mice. For the first time, we found sex-specific differences in duodenal morphology. HFD feeding reduced microvilli height in Tff3-deficient females compared to that in Wt females, suggesting a possible effect on microvillar actin filament dynamics. These changes could not be attributed to genes involved in ER and oxidative stress, apoptosis, or inflammation. Tff3-deficient males exhibited a reduced cecal crypt depth compared to that of Wt males, but this was not the case in females. Microbiome-related short-chain fatty acid content was not affected by Tff3 deficiency in HFD-fed male or female mice. Sex-related differences due to Tff3 deficiency imply the need to consider both sexes in future studies on the role of Tff in intestinal function.
EVALuna2:545144